2014
DOI: 10.1590/s0102-67202014000200015
|View full text |Cite
|
Sign up to set email alerts
|

Single-port for laparoscopic gastric resection with a novel platform

Abstract: IntroductionLaparoscopic gastrointestinal resections using single-port are possible, but triangulation problems and the need of articulated instruments difficult the procedures.AimTo present a surgical alternative using single-port laparoscopic device on gastric resection.TechniqueThe patient is placed in a supine and reverse Trendelenburg position with surgeon between patient's legs. First assistant was on the right side of the patient with the monitor placed on the patient's cranial side. With the patient un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These can be achieved through an open or a minimally invasive approach. 7 Nineteen patients with GDCs treated by a laparoscopic approach have been reported in the pediatric literature up to now (Table 1). [1][2][3][8][9][10][11][12][13][14] Three cases had a prenatal diagnosis and more than two-thirds were symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…These can be achieved through an open or a minimally invasive approach. 7 Nineteen patients with GDCs treated by a laparoscopic approach have been reported in the pediatric literature up to now (Table 1). [1][2][3][8][9][10][11][12][13][14] Three cases had a prenatal diagnosis and more than two-thirds were symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Machado et al [ 7 ] first reported laparoscopic resection of gastric duplication, followed by Tayar et al [ 8 11 ]. However, laparoscopic resection of gastric duplication cysts in newbrons is rarely reported.…”
Section: Discussionmentioning
confidence: 99%